A visible-light-induced cascade reaction of etherification/C–C cyclization: efficient synthesis of dibenzo[b, d]oxepin-7(6H)-ones. Issue 13 (15th March 2019) - Fu, Wanyong; Yu, Aixia; Jiang, Hongshuo; Zuo, Minghui; Wu, Hongfeng; Yang, Zhongwen; An, Qi; Sun, Zhizhong; Chu, Wenyi
Abstract : A visible-light-induced palladium-catalyzed cascade reaction was developed by etherification/C–C coupling cyclization of α-bromoacetophenones with phenols. Abstract : A visible-light-induced palladium-catalyzed cascade reaction was developed by etherification/C–C coupling cyclization of α-bromoacetophenones with phenols. A series of dibenzo[ b, d ]oxepin-7(6 H )-one derivatives were efficiently synthesized by using this method in good yields. Furthermore, this method was applied to the synthesis of protosappanin A. The protocol has advantages such as simple reaction conditions, wide range of substrates and high reaction efficiency.